Prestigegüter entlang der Seidenstrasse? : Prestigegüter entlang der Seidenstrasse? - Selbitschka, Armin (Asiatische Forschungen ;, 2014)
One often reads about the prestige of silk or other exotic goods that were once transmitted along the Silk Road. In particular, the spectacular finds of the last twenty years in the northwestern Chinese Tarim Basin (today's Xinjiang Autonomous Region) contributed to this. Some of them could be admired in the Mannheim exhibition "Origins of the Silk Road" in 2008. But what is meant by the "prestige" of the goods? How can prestige goods be distinguished from luxury goods or status symbols? And: Is this even possible archaeologically? Armin Selbitschka's study addresses these questions with a comprehensive analysis of several burial grounds in the Lopnor area, in Niya, Yingpan and Zhagunluke from the 2nd to the early 5th century AD The material basis is a catalog of the graves that can be evaluated, which for the first time brings together all available information on the respective burials and presents them graphically on corresponding panels. Figures and maps also illustrate the most important finds and findings: The historical background of the exchange between East and West can be deduced by reconstructing the relations between the Tarim Basin and China. Selbitschka evaluates Chinese written sources just as carefully as the Indigenous Kharosthi documents.